2017
DOI: 10.1111/apha.13001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female sex hormones on folic acid–induced anti‐angiogenesis

Abstract: Female sex hormones interrupt the FA-induced anti-angiogenic action through receptor-receptor interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Since angiogenesis is critical for placental function and development, we verified expression changes of several genes involved in angiogenesis, including 18 genes in the HIF pathway, VEGF pathway, S1P signaling, extracellular matrix formation, or other functions known to affect vascular health. Some studies have reported the impact of folate on angiogenesis, [13,14] but these studies were largely in vitro whereas our work examined folate intake in vivo. Furthermore, the impact of folate on expression of the afore-mentioned genes in angiogenesis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since angiogenesis is critical for placental function and development, we verified expression changes of several genes involved in angiogenesis, including 18 genes in the HIF pathway, VEGF pathway, S1P signaling, extracellular matrix formation, or other functions known to affect vascular health. Some studies have reported the impact of folate on angiogenesis, [13,14] but these studies were largely in vitro whereas our work examined folate intake in vivo. Furthermore, the impact of folate on expression of the afore-mentioned genes in angiogenesis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[11] FA can promote angiogenesis, [12] although some studies have suggested an anti-angiogenesis role. [13,14] Placenta can affect fetal organ development, including brain. Many neurobehavioral disorders trace their origin to placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Another female sex‐specific effect has recently been described by Lee et al, who report an antiangiogenic effect of folate, which seems to be counteracted by pregnancy‐related female hormones . Further research is needed to, in detail, observe and interpret potential related effects in human subjects.…”
mentioning
confidence: 88%
“…Upon binding to the VEGF receptor 2 (VEGFR2) on ECs, VEGF activates quiescent ECs and initiates angiogenesis, ensuring the reestablishment of oxygen and nutrients in the tissue [36,37]. However, other bioactive molecules, including growth factors [38], cytokines [39,40], hormones [41], and non-coding RNAs, such as microRNAs (miRNA) and long non-coding RNAs (lncRNA), also regulate angiogenesis [42].…”
Section: Endothelial Function Is Versatilementioning
confidence: 99%